Analisis Kontribusi Pangan dan Produk Pangan Olahan Terhadap Tingkat Kecukupan Zat Gizi dan Status Gizi Pada Mahasiswa Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian, Universitas Halu Oleo Tahun 2019 - Dila, Muhammad; Ansharullah, Ansharullah; Faradilla, RH Fitri (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2022)
ABSTRACTThis research aims to study the relationship between socio economic status (pocket money, food expenditure, and parents' income) and the adequacy of nutrients and nutritional status of students of the Department of Food Science and Technology, Faculty of Agriculture, Halu Oleo University. Food intake was obtained from interviews using a questionnaire with the diary food method. Determination of the amount of nutrient intake was done using the Nutrisurvey application. After that, determining the level of nutritional adequacy was done by comparing the total nutrient intake in 1 day with the Nutrition Adequacy Rate (RDA) in 1 day. The results showed that the fulfillment of nutrition of students with underweight, normal and overweight nutritional status was at a percentage < 80%. The data shows that the level of nutritional fulfillment of students of the Department of Food Science and Technology is lacking. Except for the level of consumption of vitamin A, the average level of consumption of students with poor nutritional status, normal, and overweight are in the percentage of 82-83%, this shows that the fulfillment of vitamin A nutrition in Food Science and Technology Students is quite adequate. Processed food products contribute (15.80-15.90, 12.42-12.47, 15.52-15.57, 18.44-18.52, 17.45-17.91, 33.77- 34,) on energy, protein, fat, carbohydrates, vitamin A, and sodium. In addition, there is no relationship between socioeconomic (allowance, food expenses, and parents' income) status on the level of nutrient adequacy and nutritional status of students of the Department of Food Science and Technology, Faculty of Agriculture, Halu Oleo University.Keywords: Food, nutritional status, nutritional intake, nutritional adequacy rate.ABSTRAKPenelitian ini bertujuan untuk mempelajari hubungan status sosial ekonomi terhadap tingkat kecukupan zat gizi mahasiswa Jurusan Ilmu dan Teknologi Pangan Fakultas Pertanian Universitas Halu Oleo. Asupan makanan diperoleh dari hasil wawancara menggunakan kuesioner dengan metode diary food. Penentuan jumlah asupan nutrisi dilakukan dengan menggunakan aplikasi Nutrisurvey. Setelah itu, penentuan tingkat kecukupan gizi dilakukan dengan membandingkan total asupan zat gizi dalam 1 hari dengan Angka Kecukupan Gizi (AKG) dalam 1 hari. Hasil penelitian menunjukkan bahwa pemenuhan nutrisi mahasiswa dengan status gizi kurang, normal dan kegemukan berada pada persentase < 80%. Data ini menunjukan bahwa tingkat pemenuhan nutrisi mahasiswa Jurusan Ilmu dan Teknologi Pangan tergolong kurang. Kecuali pada tingkat konsumsi vitamin A, rata-rata tingkat konsumsi Mahasiswa dengan status gizi kurang, normal, dan kegemukan berada pada persentase 82-83%, hal ini menunjukan pemenuhan nutrisi vitamin A pada Mahasiswa Jurusan Ilmu dan Teknologi Pangan tergolong cukup. Produk pangan olahan berkontribusi sebesar (15,80-15,90, 12,42-12,47, 15,52-15,57, 18,44-18,52, 17,45-17,91, 33,77-34,) terhadap energi, protein, lemak, karbohidrat, vitamin A, dan natrium. Hasil penelitian menunjukkan tidak terdapat hubungan antara status sosial ekonomi (uang saku, pengeluaran pangan, dan penghasilan orang tua) terhadap kecukupan zat gizi dan status gizi mahasiswa Jurusan Ilmu dan Teknologi Pangan Fakultas Pertanian Universitas Halu Oleo.Kata kunci: Pangan, tingkat kecukupan gizi, status gizi, angka kecukupan gizi.